Signwriting: Ornament as visual language communicative decoration. Issue 1 (1st August 2019) - Goodwin, Amy
This article argues for the use of decorative signwriting as both ornamental and communicative. This examination will be twofold: first, a series of images of twentieth century signwriting in the fairground industry will be offered to this argument: all signwriting is purposefully applied, as decoration, in order to communicate, but unpicking the visual styles will unveil the hidden meanings, expanding the communicative intentions. Secondly, works of signwriting produced and installed as an archive as illustrated space will be dissected to expand on the argument being made. The archive as illustrated space is a framework being theoretically structured and then applied in practice within my Ph.D. enquiry. It advances the theories and workings of both the archive and artistic archive: the space facilitates the collation of dubious and disputed narratives, alongside archival fragments: told through communicative signwriting, it demands the participation of the viewer in its installation. Using the methodology of this practice-led research will contribute to confirming how the application of a visual language to signwriting enables the production of works that are both ornamental and communicative.This argument has been formed, primarily, due to my informed fairground position: embedded within fairground heritage my upbringing has established an appreciation for its rich history, which is reflected in my practice, which blends traditional signwriting and illustrative storytelling. This informed fairground position, combined with my Ph.D. enquiry, enriches the analysis and understanding of the practice-led research within the realm of this article: offering a valuable opportunity to not only comment on the historical works presented, but also to showcase an exploration of how to apply this visual production to contemporary, installation situations.